The CXCR4/SDF-1 Axis in the Development of Facial Expression and Non-somitic Neck Muscles - Yahya, Imadeldin; Morosan-Puopolo, Gabriela; Brand-Saberi, Beate (Frontiers in Cell and Developmental Biology, 2020)
Trunk and head muscles originate from distinct embryonic regions: while the trunk muscles derive from the paraxial mesoderm that becomes segmented into somites, the majority of head muscles develops from the unsegmented cranial paraxial mesoderm. Differences in the molecular control of trunk versus head and neck muscles have been discovered about 25 years ago; interestingly, differences in satellite cell subpopulations were also described more recently. Specifically, the satellite cells of the facial expression muscles share properties with heart muscle. In adult vertebrates, neck muscles span the transition zone between head and trunk. Mastication and facial expression muscles derive from the mesodermal progenitor cells that are located in the first and second branchial arches, respectively. The cucullaris muscle (non-somitic neck muscle) originates from the posterior-most branchial arches. Like other subclasses within the chemokines and chemokine receptors, CXCR4 and SDF-1 play essential roles in the migration of a number of various tissues during development. CXCR4 as receptor together with its ligand SDF-1 have mainly been described to regulate the migration of the trunk muscles. This review first underlines our recent understanding of the development of the facial expression (second arch-derived) muscles, focussing on new insights into the migration event and how this embryonic process is different from the development of mastication (first arch-derived) muscles. Other muscles associated with the head, such as non-somitic neck muscles derived from muscle progenitor cells located in the posterior branchial arches, are also in the focus of this review. Implications on human muscle dystrophies affecting the muscles of face and neck are also discussed.